Association of Growth hormone gene polymorphisms (T3199C) SNP on productive and physiological performance in Hubbard broiler chicken - , I.Q, AL-kreem; F. Muhammad, M.; AL-Anbari, N.N (Journal of Kerbala for Agricultural Sciences, 2017)
In this study commercial broiler hybrid (Hubbard) was used to detect the T3199C SNP in the fourth intron of chicken GH gene and investigate its effect on the productive and physiological performance in broiler chicken. PCR- RFLP method was used to identify this SNP. The results revealed that two genotypes were found when using of Msp1 restriction enzyme wild genotype TT and heterozygous TC. Highly significant difference (p<0.01) was found between the distribution of the different genotypes, the genotype TT had the highest percentage followed by TC and allele T had the superiority over allele C, no significant effect of the two genotypes on the productive traits in broiler breed of study, significant effect (p<0.05) of the two genotypes were found on the total protein concentrations of blood serum at 14 days of age and on the total protein and glucose concentration of blood serum at 42 days of age.